Cross-linking of dialdehyde carboxymethyl cellulose with silk sericin to reinforce sericin film for potential biomedical application. (15th May 2019) - Wang, Peng; He, Huawei; Cai, Rui; Tao, Gang; Yang, Meirong; Zuo, Hua; Umar, Ahmad; Wang, Yejing
Graphical abstract: Highlights: Sericin is cross-linked with DCMC through Schiff's base reaction. Cross-linking of sericin with DCMC reinforces sericin film properties. DCMC/SS film has excellent hydrophilicity and biocompatibility. Abstract: Developing biomaterials based on the natural biomacromolecule silk sericin from Bombyx mori cocoon is of great interest for biomedical application. Dialdehyde carboxymethyl cellulose (DCMC) is derived from periodate oxidation of carboxy- methyl cellulose. Here, we developed a novel strategy of cross-linking of sericin with DCMC via the Schiff's base reaction. Fourier transform infrared spectroscopy and scanning electron microscopy indicated the formation of Schiff's base via the blending of sericin and DCMC. The mechanical properties tests suggested the covalent cross-linking effectively enhanced the tensile strength of sericin. The swelling test and water contact angle indicated the DCMC/SS film had excellent hydrophilicity, swellability. Additionally, we demonstrated the DCMC/SS film had excellent blood compatibility, cytocompatibility and promoting cell proliferation activity by the hemolysis ratio analysis, cell adhesion, cells viability and proliferation assays. The prepared DCMC/SS film has shown great promise in biomedical applications such as wound dressing, artificial skin and tissue engineering.